Pengaruh Harga dan Pandemi Covid-19 Terhadap Permintaan dan Penawaran Bawang Merah di Indonesia - Khaya Bastanta Parangin Angin Sukatendel; Soetriono Soetriono; Adang Agustian (University of Jember, 2023)
The excess supply of shallots due to the increase in harvest area in Indonesia in 2019-2020 resulted in a gap between supply and demand, resulting in price fluctuations over time. The price fluctuations that occurred plus the covid-19 pandemic in early 2020 caused low purchasing power and reduced household consumption. The study aims to determine the effect of prices and the Covid-19 pandemic on the demand and supply of shallots in Indonesia. The data used is time series data. Data analysis using multiple linear. The results showed that the demand for shallots in Indonesia increases every year because this commodity is always needed every day, but the demand for shallots is not matched by stable and evenly distributed production in each region every month. Prices and the covid-19 pandemic affect the demand for shallots in Indonesia significantly and significantly, there are also other factors, namely chili prices which have a negative effect on demand, and per capita income which has a positive effect on demand. Prices and the covid-19 pandemic partially have no significant effect on shallot supply in Indonesia. The variable that has the strongest influence on shallot supply in Indonesia is the harvest area variable.